Association between longitudinal tooth fractures and visual detection methods in diagnosis. (October 2020) - Kim, Jae-Hoon; Eo, Soo-Heang; Shrestha, Reetu; Ihm, Jung-Joon; Seo, Deog-Gyu
Abstract: Objectives: This study investigated the distribution of longitudinal tooth fractures (LTFs) according to the patient's age and analyzed the association between visual detection methods and the types of LTFs. Methods: Patients with symptomatic teeth with LTFs were examined at the department of conservative dentistry in a dental hospital from September 1, 2009 to March 31, 2014. Naked eye examination, staining with a dye, operating microscopy, transillunimation, and periapical radiography were used to identify the fracture lines. Diagnostic surgery was performed to visualize the fracture line in some cases with vertical root fractures. The final diagnosis was based on the American Association of Endodontists (AAE) classification: cracked tooth, fractured cusp, split tooth, and vertical root facture. The probability density function for each type of LTF was calculated to assess the risks of LTF development according to age. The association between the detection methods and types of LTFs was identified using the association plot. Results: A total of 245 teeth with LTFs were enrolled. Overall, 71.8% of LTFs was observed in patients aged 40–69 years, and 65.7% of LTFs were diagnosed as cracked teeth. The mean age in patients with cracked teeth was 49.3 years, while the mean age in patients with fractured cusps was 59.1 years. A significant association was observed between the detection method and type of LTF ( p  < 0.001). Conclusions: Cracked tooth was the most common type of LTF. The probability of occurrence of cracked teeth peaked in patients aged approximately 50 years, while the probability of occurrence of fractured cusps peaked in patients aged approximately 60 years. Cracked teeth were detected most often using transillumination. Clinical significance: LTFs occurred mostly in patients aged 40 years and older. Transillumination is useful for the diagnosis of cracked teeth.